Stakeholder Engagement For Business Sustainability - Jamil Farhas, Rizqon; Rabialdyi, Fakhri; Laowe, Dhya Nadia (Journal of Social and Community Service, 2023)
Companies need to understand and manage relationships with stakeholders in achieving goals and prepare conflict reports that cover social, environmental and economic aspects in accordance with POJK No. 51/POJK.03/2017. The 3P (Profit, Planet, People) concept from Elkington (1997) emphasizes the balance between economic profit, environmental sustainability and social welfare. Binus Business School held a public lecture entitled "Stakeholder Engagement for Sustainability" with 757 participants to increase understanding of stakeholder engagement and relevant regulations, using examples of companies such as Tesla and KFC. The method used is the delivery of research-based material. The results of the discussion showed that government regulations, including Law no. 32 of 2009 concerning Environmental Protection and Management, plays an important role in regulating corporate social responsibility (CSR). Compliance with these regulations is essential to maintain social and environmental responsibility. In conclusion, companies have a dual role in society: they can provide great benefits through innovation and job creation, but they can also have negative impacts regarding the environment and human rights. It is important for companies to comply with regulations and take responsible steps to strike a balance between the positive benefits and negative impacts of their operations.